HTRA1 promoter polymorphism predisposes Japanese to age-related macular degeneration - Yoshida, Tsunehiko (Molecular Vision, 2007)
PURPOSE: To study the effect of candidate single nucleotide polymorphisms (SNPs) on chromosome 10q26, recently shown to be associated with wet age-related macular degeneration (AMD) in Chinese and Caucasian cohorts, in a Japanese cohort. METHODS: Using genomic DNA isolated from peripheral blood of wet AMD cases and age-matched controls, we genotyped two SNPs, rs10490924, and rs11200638, on chromosome 10q26, 6.6 kb and 512 bp upstream of the HTRA1 gene, respectively, using temperature gradient capillary electrophoresis (TGCE) and direct sequencing. Association tests were performed for individual SNPs and jointly with SNP complement factor H (CFH) Y402H. RESULTS: The two SNPs, rs10490924 and rs11200638, are in complete linkage disequilibrium (D'=1). Previous sequence comparisons among seventeen species revealed that the genomic region containing rs11200638 was highly conserved while the region surrounding rs10490924 was not. The allelic association test for rs11200638 yielded a p-value <10(-11). SNP rs11200638 conferred disease risk in an autosomal recessive fashion: Odds ratio was 10.1 (95% CI 4.36, 23.06), adjusted for SNP CFH 402, for those carrying two copies of the risk allele, whereas indistinguishable from unity if carrying only one risk allele. CONCLUSIONS: The HTRA1 promoter polymorphism, rs11200638, is a strong candidate with a functional consequence that predisposes Japanese to develop neovascular AMD.